Development of Ethnoscience-Based E-Modules on Arabica Java Ijen-Raung Coffee Plant to Improve Learning Outcomes of Grade IV Elementary Students - Sofian*, Aulia Dwi Putri; Nuriman, Nuriman; Wardani, Rizki Putri; Ramasamy, Sujatha (Jurnal Pendidikan Sains Indonesia, 2025)
Indonesia is a country that has a rich culture and abundant natural resources. In the globalization era, local cultures are significantly fading due to the incoming influence of foreign cultures. Education is a tool to bridge knowledge and values embedded in a place to the community. Ethnoscience is an approach that connects local culture and scientific knowledge. This study uses an ethnoscience approach to preserve knowledge derived from natural potential in Indonesia. Integrating ethnoscience concepts in learning helps students improve their learning outcomes and master 21st-century skills that are relevant today. This study aims to develop an ethnoscience-based e-module on the arabica java ijen-raung coffee plant. This module highlights the unique methods of planting Arabica coffee in the Ijen highlands. This study examines the validity, effectiveness, and practicality of using an ethnoscience-based e-module on the arabica java ijen-raung coffee plant to improve learning outcomes of grade IV elementary students. This quantitative development research uses the ADDIE model, which contains analysis, design, development, implementation, and evaluation processes. The result of this research shows a 93% validity score. Effectivity score using N-Gain methods earns 79,2822 included in the effective category. Practicality score earns 94% including in excellent category. Based on this result. It can be concluded that the ethnoscience-based e-module on the arabica java ijen-raung coffee plant is valid, effective, and practical to improve student learning outcomes for grade IV elementary school students